TRADISI TABUIK DI KOTA PARIAMAN - Maezan Kahlil Gibran; Syamsul Bahri (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2015)
Culture is complex that includes knowledge, art, moral, legal, customs andother skills and habits by human members of society. The tradition is a habit of socialderived from a generation to generation other through the process of socialization.The tradition of determining the values and moral society, because tradition are therules about what is right and what is wrong according to residents. Tabuik is acultural heritage in the form of ritual ceremony, which is growing in Pariaman sinceabout two centuries ago. Tabuik is a ceremony or the celebration commemorating thedeath of Husain, but then develop into a culture of Pariaman as in the elements ofculture Minangkabau. For the Pariaman ceremony is not a faith (the trust concernedwith the divined or the revered), the implementation of the just for the ceremony tocommemorate the death of Husain. The important thing of the celebration of tabuik isthe implementation of the party who by the Pariaman called batabuik or mahoyaktabuik. The celebration tabuik of ritus-ritus or a series of the ceremony begins fromthe rite maambiak tanah into the river, maambiak/manabang batang pisang, maatam,marandai, maarak jari-jari, maarak saroban, tabuik naiak pangkek, maoyak tabuik,to be closed with a rite mambuang tabuik into the sea. Ritus-ritus embodied in theform of the procession. Range of time used to it procession between 10 to 14 days atthe beginning of Muharram, can even more than that. In the implementation of thetradition tabuik since the first will be conducted until now had a change in terms ofkesakralan and spiritual communities in Pariaman in the procession tabuik, as forchanges in the tradition tabuik is as follows; Kepala Burak, Auang Tuo Tabuik, TheIn Kerangka Tabuik, Pembungan Tabuik, and Hoyak Tabuik. At the dawn of theimplementation of tabuik, tabuik is carried out some of the ceremony is sacred andcontains the value of the high, for the perpetrators tabuik of preparing the showtabuik as celebrate religious holidays. But the implementation of the tabuik now moreto show the entertainment value or tourism of the Pariaman.The key word: Tradition, Change, Tabuik